2002
DOI: 10.1073/pnas.022641099
|View full text |Cite
|
Sign up to set email alerts
|

Potent antiarthritic properties of a glucocorticoid derivative, NCX-1015, in an experimental model of arthritis

Abstract: Here, we describe the improved antiarthritic properties of a nitric oxide-releasing derivative of prednisolone that includes a sparing of the effects on bone. Glucocorticoids are widely used in the treatment of chronic inflammatory pathologies, but their use is often accompanied by side effects, including osteoporosis. Recently, a new steroid able to release low levels of nitric oxide showed potent inhibition of leukocyte trafficking and chemokine generation in models of acute inflammation. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 33 publications
3
53
0
4
Order By: Relevance
“…It has been shown in murine arthritis models that NCX-1015 caused anti-inflammatory effects 10-fold stronger than conventional prednisolone. At the same time fewer side effects are anticipated on the bone compartment, since elevated bone resorbing activity of rat primary osteoclasts was observed for prednisolone but not for NCX-1015 [42][43][44]. In order to explain the strong anti-inflammatory effects of nitro-steroids, posttranslational modification of GCR through tyrosine nitration is suggested [42].…”
Section: Nitro-steroidsmentioning
confidence: 99%
“…It has been shown in murine arthritis models that NCX-1015 caused anti-inflammatory effects 10-fold stronger than conventional prednisolone. At the same time fewer side effects are anticipated on the bone compartment, since elevated bone resorbing activity of rat primary osteoclasts was observed for prednisolone but not for NCX-1015 [42][43][44]. In order to explain the strong anti-inflammatory effects of nitro-steroids, posttranslational modification of GCR through tyrosine nitration is suggested [42].…”
Section: Nitro-steroidsmentioning
confidence: 99%
“…We also observed a significant reduction in systemic toxicity of the NO-releasing derivative of flunisolide versus the parent drug; thus, adrenal atrophy and the reduction of body weight gain associated with daily administration of flunisolide were substantially reduced in rats treated with NCX-1024. In studies of NO-releasing prednisolone, Paul-Clark et al (2002) observed a significant reduction of collagen-induced arthritis associated bone and cartilage erosion in comparison with that seen in rats treated with prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of osteocalcin, a marker of bone formation, were determined using a commercially available IRMA specific for rats (Immutopics, San Clemente, CA). A competitive enzyme immunoassay (Metra Biosystems, Mountain View, CA) was used to evaluate pyridinoline, a marker of cartilage and bone destruction (29)(30)(31)(32).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, serum pyridinoline levels increased almost 2-fold during the chronic phase of SCW arthritis ( Figure 4A). Treatment with PTHrP antibody inhibited the SCW-induced increase in pyridinoline, a degradation product of cartilage and bone that correlates with destruction of both of these tissues in animal models of arthritis (29)(30)(31)(32) (Figure 4A). …”
Section: Pthrp Expression In Scw-induced Arthritismentioning
confidence: 99%